Engineering mechanics : statics & dynamics - Costanzo, Francesco , 1964-; Gray, Gary L.; Plesha, Michael E. (McGraw-Hill Higher Education, 2010)
This is a full version; do not confuse with 2 vol. set version (Statistics 9780072828658 and Dynamics 9780072828719) which LC will not retain